Municipal Management Model to Minimize Physical Gender Violence Against Women Systematic Literature Review - Villalta, Mgs. Leonardo Orleans Labre; Gavilanes, Mgs. Luis Antonio Villalta; Llongo, Abg. Angel Rodolfo Pilco; Llauce, Dra. Cecilia Teresita de Jesús Carbajal (Journal of Ecohumanism, 2024)
This systematic review aims to analyze the influence of a municipal management model to minimize physical gender violence against women. The seriousness of this problem is highlighted in the Latin American context, where cultural and socioeconomic factors aggravate the situation, mainly in Ecuador. This study focuses on how municipal management models can influence the prevention and attention of physical gender violence. The PRISMA method was used to structure the review, analyzing relevant literature from 2019 to 2023 in databases such as Scopus, SciELO, Redalyc, Dialnet, Erih Plus, Latindex and the University César Vallejeo. The results found indicate that physical gender violence, which includes attacks such as hitting and pushing, is deeply rooted in social structures that perpetuate male domination. Likewise, other findings indicate that management models that encourage citizen participation are more effective in designing public policies that address the specific needs of women. However, significant obstacles were identified, such as the lack of resources and training, that prevent an adequate response to this problem. The review concludes that it is essential to strengthen municipal management models and promote a comprehensive approach that addresses gender violence and implements concrete actions to guarantee a safe environment free of violence for all women.